Life without Barriers: Prospects and Changes in the Situation of Children with Disabilities and Lifelong Disabled Persons - Klochko E.Y (Moscow State University of Psychology and Education, 2016)
The article shows the role of Russian ratification of the UN Convention on the Rights of Persons with Disabilities. Problem analysis of kind of services for chil- dren with disabilities and lifelong disabled persons is performed using a schema "Alternative living models for a lifelong disabled person in Russia". The article demonstrates the main content of early intervention programs and the role and place of a multidisciplinary team of program experts. We discuss the main aspects of the problems related to education for disabled children, the features of linkage between social services and social support for children with disabilities and families raising them. Attention is paid to the development and widespread implementation of hospital- substituting technologies. The article presents con- cept of a pilot project of the Foundation for children in difficult life situation to facilitate the social adaptation of disabled persons. Author made a conclusions on increasing authorities' attention to disable person's needs, the need for change in the current legislation according to UN Convention, and annexations to federal legislation governing the rights of disabled children and lifelong disabled persons, the need to develop public policies using all available resources and the experience of socially oriented NGOs primarily.